Friedrich Max Müller, A Life Devoted to the Humanities. - Lourens Peter van den Bosch (Numen Book Series, 2002)
Friedrich Max Müller was one of the great scholars of the nineteenth century. His studies on the history and nature of religion were of great interest to both scholarly and more popular circles, and he was for a long time an influential figure in the cultural life of Victorian Britain. Therefore, a new study of his life and especially of his works needs no apology. The book gives a survey of Müller's life and his main ideas on language, mythology, religion, Christianity and the missions, as well as his philosophy of religion. The last chapter deals with the legacy of Müller's ideas in the twentieth century. The book is particularly useful for historians of religion interested in the origin of the science of religion and for historians specialized in the history of ideas.